Cholinesterase, α-Glucosidase, α-Amylase, and Tyrosinase Inhibitory Effects and Antioxidant Activity of Veronica officinalis Extracts - Nuraniye ERUYGUR; Esra UÇAR (Türkiye Tarımsal Araştırmalar Dergisi, 2018)
In this study, inhibition ability of Veronica officinalis extracts against Alzheimer’s disease-related enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), diabetes mellitus related enzymes α-glucosidase and α- amylase and antioxidant of Veronica officinalis were investigated. To the best of our knowledge, there are no previous studies on the enzyme inhibition activities of the V. officinalis extracts. For this aim, V. officinalis extracted with methanol and water by maceration method and their antioxidant activities were evaluated by DPPH (2,2-Diphenyl-1-picrylhydrazyl), ABTS [2,2′- Azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid)] radical scavenging assays, total phenol, total flavonoid content, iron chelating and ferric reducing power assays. The enzyme inhibition activity was performed with 96-well plate method. According to the obtained results; the plant extracts have good antioxidant effects. In the same time, the water extract have stronger inhibition activity against AChE, BuChE and α-glucosidase, α-amylase, and tyrosinase than methanol extract. The experimental findings indicated that the water extract exerted the higher α-glucosidase, α-amylase and tyrosinase (82.07 ± 2.91, 63.61 ± 3.93 and 47.47 ± 0.53 at 2 mg mL-1, respectively) inhibition than reference drugs. The obtained results demonstrate that this plant has a significant potential for improving pharmaceutical formulations.